ANALYSIS OF PRACTICE FAMILY-OWNED COMPANIES IN REPUBLIC OF UZBEKISTAN - Umida Tashtanova Elmurod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Family Business is considered the world’s oldest business institution and a special form of organization of activity, with own history and many examples of success, among which the most famous are large family corporations and holdings. At the same time, it is important to study the features and trends in the development of this form of organization in small and medium-sized business. This phenomenon is currently in the initial stages of research; many definitions are not established and are debatable. For a business to be successful, it must be family-owned. However, family business is defined differently in different sources and by different scholars. According to Demassis et al. a business in which multiple members of the same family have influence on the firm’s strategic actions and directions . In another definition a family business is defined as any business in which a majority of the ownership or control lies within a family, and in which two or more family members influence the direction of the business, through ownership, management, or both .